Total nitrogen and humic substances in aggregates of soils with onion crops under no-tillage and conventional tillage systems (2018)
The objective of this study was to evaluate the soil total nitrogen (TN), and N contents in humic substances (HS) of the organic matter in aggregates of soils cultivated with onion under no-till system for horticulture (NTSH) and conventional tillage system (CTS), comparing with an area of forest. The evaluated treatments were natural vegetation (control), 100% black oats, 100% rye, 100% oilseed radish, intercrop of oilseed (14%) + rye (86%), intercrop of oilseed (14%) + black oats (86%), area under CTS of onion for ±37 years, and area with secondary forest for ±30 years. Five years after the NTSH implementation, undisturbed soil samples from the layers 0-5 cm, 5-10 cm, and 10-20 cm were collected; these samples presented aggregate sizes between 2.0 mm and 8.00 mm. The TN, and N contents of the HS were subdivided into fulvic acids (N-FA), humic acids (N-HA), and humin (N-HU) fractions. The change from CTS to NTSH increases the TN and N-HU contents in the 0-5 cm soil layer. The intercrop of oats and oilseed radish, used as soil plant cover species in NTSH, presented a greater increase in N-HU (0-20 cm) than the other treatments. Black oats, and natural vegetation presented a greater increased in N-HA, and N-FA contents, respectively, in the 10-20 cm layer, than the other treatments in NTSH and CTS. CTS with millet as soil plant cover presented a greater increase in N-FA (0-20 cm) contents than the NTSH treatments.